2016
DOI: 10.1002/tea.21372
|View full text |Cite
|
Sign up to set email alerts
|

Pushing and pulling Sara: A case study of the contrasting influences of high school and university experiences on engineering agency, identity, and participation

Abstract: This manuscript reports a longitudinal case study of how one woman, Sara, who had previously considered dropping out of high school, authored strong mathematics and science identities and purposefully exhibited agency through her experiences in high school science. These experiences empowered her to choose an engineering major in college; however, her introductory university engineering experiences ultimately pushed her out of engineering. Drawing on critical agency theory, we argue that by paying careful atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 81 publications
(69 reference statements)
1
79
0
1
Order By: Relevance
“…The GSM model implies that they, instead of being attracted, rather feel demotivated by ordered contexts, particularly if these contexts are complicated. These may be the students that perceive ordered systems as stable, rigid, and fixed (Holmegaard, Madsen, & Ulriksen, ), feel anxious and hopeless (González, Fernández, & Paoloni, ), and may even be pushed out of studies by neglected identity and agency beliefs (Godwin & Potvin, ).…”
Section: Discussionmentioning
confidence: 99%
“…The GSM model implies that they, instead of being attracted, rather feel demotivated by ordered contexts, particularly if these contexts are complicated. These may be the students that perceive ordered systems as stable, rigid, and fixed (Holmegaard, Madsen, & Ulriksen, ), feel anxious and hopeless (González, Fernández, & Paoloni, ), and may even be pushed out of studies by neglected identity and agency beliefs (Godwin & Potvin, ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have shed light on the understanding of the curriculum experiences associated with sustainable agency beliefs in the context of engineering education. For example, a longitudinal case study by Godwin and Potvin [63] described how high school experiences helped a young woman build her agency beliefs and select an engineering major in college, while her experiences of engineering education weaken the agency beliefs she built and impelled her to quit engineering after her first year in college. Baugher et al [64] further revealed that international service learning through formal curricular experiences was closely correlated with engineering students' agency beliefs.…”
Section: Mediating Role Of Sustainable Agency Beliefsmentioning
confidence: 99%
“…To date, significant qualitative work has advanced our understanding of how students describe identity development and what that means for their development as professional engineers [10][11][12][13][14] . This prior work provides a strong basis for understanding how identity influences important outcomes like student recruitment and retention.…”
Section: Introductionmentioning
confidence: 99%